THE FEATURES OF PRIMARY-SCHOOL-AGE CHILDREN’S NEGATIVE EMOTIONAL EXPERIENCES - Gud, Hanna (PSYCHOLOGICAL JOURNAL, 2019)
In recent years, research in emotions becomes the more and more important scientific and practical task because emotionality is one of the most important features in the structure of a schoolchild’s personality. However, primary-school-age children’s negative emotional experiences, examined in this article, are presented insufficiently in psychological studies, because the concept of "negative emotions" is not defined clearly and its correspondence with "negative emotional experiences", "anxiety", "fears", psychical health, etc. are not determined, in spite of the fact that these emotions and emotional states are important for development of children’s emotional sphere. At the primary-school age, according to the leading national psychologists, many emotions appears, so children are able to experience joy, anger, shame, fear, anxiety, trust, disappointment, pleasure, pride. The existing chain of failures experienced by a child or, on the contrary, successes (in learning, communication) leads to the formation of stable affective complexes - a sense of inferiority, bitterness, etc. Generalization of emotions appears at this age. Further, these formations can be changed or disappear with the accumulation of experience and socialization on the micro-, macro-, and meso-levels. But some of them, being supported by some life events, are fixed in the structure of a personality and affect self-appraisal and the level of aspiration. Thus, negative emotional experiences of primary schoolchildren are caused by unpleasant subjective emotions, which start the mechanisms of adaptive behaviour aimed at elimination of physical and psychological causes of such experiences. The following socio-psychological factors: lack of emotional contact between parents and their children, limited communications between parents and their children, adults’ ignorance on age and individual psychological peculiarities; inadequate parental styles (symbolic, authoritarian, emotional-repulsive); appearance of new children’s activities that demand new relationships with parents, teachers, peers; influence of various subcultures, mass media and computer games; existing barriers in communications, and styles of children’s relations can influence emotional development both in the positive and negative ways and can cause increased emotional tension and lead to appearance of persistent negative psychic characteristics. When children enter to school, their experiences acquire a new meaning: interpersonal relations are established, emotions becomes hierarchically structured, a sense of self-importance appears; therefore, there is a discrepancy between inner life (emotional experience, feelings, mood, etc.) and external behaviour. The article substantiates that negative emotional experiences affect the situation of failure, uncertainty in oneself, etc. The carried out pilot study has confirmed our assumption concerning negative experiences caused by lack of children’s emotional communications in their families and at the learning environment.